2016
DOI: 10.5219/540
|View full text |Cite
|
Sign up to set email alerts
|

Comparable efficiency of different extraction protocols for wheat and rye prolamins

Abstract: The identification and quantification of cereal storage proteins is of interest of many researchers. Their structural or functional properties are usually affected by the way how they are extracted. The efficiency of extraction process depends on the cereal source and working conditions. Here, we described various commonly used extraction protocols differing in the extraction conditions (pre-extraction of albumins/globulins, sequential extraction of individual protein fractions or co-extraction of gluten prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Schalk et al, 16 reported 80-120 kDa for HMW group, 43-68 kDa for MMW group and 32-45 kDa for LMW group of gliadins, whereas 100 kDa for Dhordein, 45-65 kDa for C-hordein and 32-40 kDa for B-hordein. Socha et al, 40 showed the MW of 30-45 kDa for α/β, γ-gliadins in wheat while, 37 kDa for 40k-γ-secalins and 66.2 kDa for 75k-γ-secalins in rye ours respectively. Field et al, 12 also reported the MW of 40k-γ-secalins and 75k-γ-secalins as 33 kDa and 54 kDa respectively, while 41 also reported the MW of secalin as 35 kDa and 66 kDa, which con rms our ndings.…”
Section: Resultsmentioning
confidence: 99%
“…Schalk et al, 16 reported 80-120 kDa for HMW group, 43-68 kDa for MMW group and 32-45 kDa for LMW group of gliadins, whereas 100 kDa for Dhordein, 45-65 kDa for C-hordein and 32-40 kDa for B-hordein. Socha et al, 40 showed the MW of 30-45 kDa for α/β, γ-gliadins in wheat while, 37 kDa for 40k-γ-secalins and 66.2 kDa for 75k-γ-secalins in rye ours respectively. Field et al, 12 also reported the MW of 40k-γ-secalins and 75k-γ-secalins as 33 kDa and 54 kDa respectively, while 41 also reported the MW of secalin as 35 kDa and 66 kDa, which con rms our ndings.…”
Section: Resultsmentioning
confidence: 99%
“…solvent employed, presence of salt as in case of DuPont and rate of protein extraction (Socha et al, 2016). The work of (He et al, 2022) reported the protein content of extracted dialyzed gliadin as 85% employing alcohol extraction procedure and 6.25 conversion factor instead of 5.7 as used in the current work.…”
Section: Physiochemical Characteristicsmentioning
confidence: 94%
“…The total nonessential amino acids (TNEAA) accounted for 69.90-80.00 g/100 g of total amino acid content with the highest in Weiss extracted gliadins (74.03-80.00 g/100 g) followed by g/100 g) and Wallace (74.55-77.52 g/100 g), while lowest in DuPont extracted, gliadin (69.90-73.91 g/100 g). NEAA plays an important role in dough strengthening and are known to stabilizes the protein tertiary structure via amino acid side chain of glutamic acid and cysteine which are normally involved in the formation of hydrogen and disulfide bonding, respectively (Barak et al, 2015;Socha et al, 2016). This suggested that the Weiss extracted gliadin might have more proteinprotein interactions due to relatively higher TNEAA while DuPont extracted gliadin the least.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…To reduce the sample attached to the microtube wall, centrifugation was carried out at 13000 rpm for 1 minute. Then 20 µL of the sample was pipetted and put into the SDS -PAGE well [10,15,16].…”
Section: Determination Of Molecular Weight Of Gliadin Using Sds -Page...mentioning
confidence: 99%
“…Reducing agents that are used are sodium sulfite, sodium bisulfite, sodium metabisulfite, or a mixture of those agents [13]. Characterization of gliadin products that can be carried out includes using Fourier Transform Infrared Spectroscopy (FTIR), Reversed Phase -High Performance Liquid Chromatography (RP-HPLC) and Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS PAGE) [1,10,14,15,16,17]. This study aims to study the effect of variation in sodium sulfite concentration on the separation of gliadin from gluten.…”
Section: Introductionmentioning
confidence: 99%